Well-Being of Adolescents in De-Escalation Situation: Physical, Emotional, Social, and Academic Impact - Berasategi Santxo, Naiara; Idoiaga Mondragon, Nahia; Ozamiz-Etxebarria, Naiara; Dosil-Santamaria, Maria (Frontiers in Psychology, 2021)
The Covid-19 pandemic has changed the world we knew in recent months. In the interest of maintaining social distance, lockdown periods have been established and schools in many countries have closed their doors. In this context, the objective of this research was to analyze the well-being of adolescents in Spain after lock-down and during the de-escalation process in a holistic way; taking into account their indicators on physical, emotional, social, and academic levels. The “Well-being of Children in Lockdown” (WCL) scale was used to measure the well-being of adolescents using these same parameters (Berasategi et al., 2020). The results point out that the general well-being of adolescents in the pandemic situation was situated at an intermediate level. Taking into account the different aspects measured within the general well-being, the domains that obtained the lowest scores were the domains of addictions and playful and creative activities. Intermediate scores were also obtained in the physical activity, emotional and academic domains, with the routine and academic domains having the highest scores. Boys and younger adolescents are those who show higher scores in the general well-being. Moreover, correlations appear between academic task stress and emotions, playful and creative activities, addictions, physical activity, routine, academic and overall well-being.